Clinicopathological features of nonspecific invasive breast cancer according to its molecular subtypes - Zavyalova, M.; Vtorushin, S.; Telegina, N.; Krakhmal, N.; Savelieva, O.; Tashireva, L.; Bragina, O.; Denisov, E.; Kaigorodova, E.; Slonimskaya, E.; Choynzonov, E.; Perelmuter, V. (Experimental Oncology, 2016)
The aim of the present study was to investigate the clinical and morphological features of nonspecific invasive breast cancer according to its molecular subtypes. Materials and Methods: 163 women with nonspecific invasive breast cancer (T1–4N0–3M0) were included in the present study. Luminal A type of breast cancer was detected in 101 women, luminal B type — in 23 women, overexpression of HER2/neu was identified in 14 women and triple-negative cancer — in 25 women. Results: The study revealed that various molecular subtypes of breast cancer differ in the morphological structure, the expression characteristics of the primary tumor and the rate of lymphogenous and hematogenous metastasis. Lymphogenous metastases were more frequently (in 71%) detected in HER2/neu overexpressing breast cancer than in luminal A (41%), luminal B (39%) and triple-negative tumors (40%). Hematogenous metastasis did not depend on the morphological structure of carcinoma infiltrative component, the state of tumor stroma as well as the proliferative activity in all the investigated groups. Conclusion: The revealed clinicopathological characteristics of different molecular subtypes of invasive breast cancer allow to predict the possible outcome of the disease and select personalized treatment strategy for patients more reasonably.